2019
DOI: 10.1093/ejcts/ezz044
|View full text |Cite
|
Sign up to set email alerts
|

Pathological complete response after neoadjuvant/induction treatment: where is its place in the lung cancer staging system?†

Abstract: OBJECTIVES Prognosis for patients with non-small-cell lung cancer (NSCLC) who, after neoadjuvant/induction and surgery, have a pathological complete response (pCR) is expected to be improved. However, the place of the pCR patients in the context of the tumour, lymph node and metastasis (TNM) staging system is still not defined. The aim of this study is to investigate the long-term survival of NSCLC patients with pCR and to find their appropriate staging category within the TNM staging system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Firstly, we observed that initial single-level N2 disease is associated with improved OS. This factor was not previously explored in other series on pCR patients and seems to be a promising and easy-to-use prognostic factor in this subset of patients [10,[16][17][18]20]. Other authors have reported better survival results in patients with persistent N2 disease after IT and followed by surgery, when a single N2 station is involved [21].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Firstly, we observed that initial single-level N2 disease is associated with improved OS. This factor was not previously explored in other series on pCR patients and seems to be a promising and easy-to-use prognostic factor in this subset of patients [10,[16][17][18]20]. Other authors have reported better survival results in patients with persistent N2 disease after IT and followed by surgery, when a single N2 station is involved [21].…”
Section: Discussionmentioning
confidence: 97%
“…From a theoretical point of view, the IT in LA-NSCLC should have the following purposes: (i) to increase resectability by downstaging lung cancer, (ii) to reduce the extent of resection, (iii) to reduce the local and distance recurrence rate, by controlling microscopic distant metastastic spread, and (iv) to increase the overall survival. Robust evidence suggests that better long-term outcomes could be expected after surgery in patients who presented with a downstaging after neoadjuvant therapy (i.e., mediastinal downstaging) [8,10,13]. Although it does not represent the primary goal of neoadjuvant therapy, one of its potential outcomes is the achievement of pathological complete response (defined as the absence of any residual neoplastic cell in the surgical specimen), which represents the best scenario with the highest survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations